Ethnic diversification and neighbourhood mixing: A rapid response analysis of the 2021 Census of England and Wales. Issue 1 (16th January 2023) - Catney, Gemma; Lloyd, Christopher D.; Ellis, Mark; Wright, Richard; Finney, Nissa; Jivraj, Stephen; Manley, David
Abstract: This paper provides a rapid response analysis of the changing geographies of ethnic diversity and segregation in England and Wales using Census data covering the last 30 years (1991, 2001, 2011 and 2021), a period of significant social, economic and political change. Presenting the first detailed analysis of 2021 Census small area ethnic group data, we find that the growth of ethnic diversity at the national level is mirrored across residential neighbourhoods. Increasing numbers of neighbourhoods are home to a substantial mix of people from different ethnic groups, and this growing neighbourhood ethnic diversity has been spatially diffusing across all regions of England and Wales. We argue that to understand the ethnic mosaic across England and Wales, it is more illuminating to consider mix than majority: places labelled as 'minority‐majority' are, in fact, ethnically diverse spaces, home to sizable proportions of people from many ethnic groups. Increasing ethnic diversity is matched by decreasing residential segregation, for all ethnic groups—majority and minority. Short Abstract: This paper analyses the changing geographies of ethnic diversity and segregation in England and Wales using Census data covering the last 30 years (1991–2021). Residential segregation of all ethnic groups – White and minority – is declining. At the local level, many more neighbourhoods are ethnically diverse, and diversity has been spreading out to new locales. Places labelled as 'minority‐majority' are, in fact, ethnically diverse, home to sizable proportions of people from many ethnic groups.